EXPERIMENTAL STUDY ON INFLUENCE FACTORS OF DYNAMIC FRACTURE TOUGHNESS SIZE BASED ON CT SAMPLE - ZOU GuangPing; WU SongYang; YAN AnShi; LI YinChen; ZHANG ZhiJun; CHANG ZhongLiang (Jixie qiangdu)
In order to study the influence of compact tensile (CT) specimen size on dynamic fracture toughness test, a dynamic fracture test of 2112T4 aluminium alloy CT was carried out based on a split Hopkinson tie bar (SHTB) device. The dynamic fracture toughness of the specimen was calculated by digital speckle correlation method( DSCM) , and the correctness of this method was demonstrated by comparing the results of strain gauge method. The influence of different sizes of specimens and loading hole locations on dynamic fracture toughness was studied. The results show that the smaller the value of W/B, the smaller the dynamic fracture toughness value of CT specimens and the slower the decreasing trend. For samples of different sizes with the same W/B value, the dynamic fracture toughness gap is small. Changing the center distance of loading round hole has little influence on the experimental results of dynamic fracture toughness.